Enhanced Bézier curve-based trajectory planning for high-altitude autonomous trucks - Du Chigan; Jianbei Liu; Yang Zhao; Jianyou Zhao (PLoS ONE, 2025)
Highway freight transport is the backbone of Tibet’s logistics network, accounting for 76.4% of regional freight movement (Tibet Bureau of Statistics, 2024). Challenging alpine road conditions—characterized by steep grades, sharp curves, and narrow lanes—combine with the substantial dimensions of heavy trucks to create significant operational difficulties. Autonomous truck development offers a potential solution; however, their trajectory planning algorithms exhibit limitations in high-altitude environments. To address these challenges, we propose a novel trajectory planning method using quartic Bézier curves. These 4th-order parametric curves provide G² continuity. Our approach integrates speed profiles into a three-dimensional curve representation and employs a two-phase optimization process to ensure safety and efficiency. Simulation results demonstrate the method’s effectiveness in maintaining truck stability while enabling responsive maneuvering under Tibet’s demanding road conditions.